2017
DOI: 10.1111/jch.13051
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of fragmented QRS in hypertensive patients in the absence of left ventricular hypertrophy

Abstract: In the absence of left ventricular hypertrophy, importance of fragmented QRS complex (fQRS) in individuals with hypertension is unknown. The authors aimed to evaluate the relationship between blood pressure levels and fQRS in the absence of left ventricular hypertrophy. A total of 548 never-treated patients who underwent 24-hour ambulatory blood pressure monitoring were enrolled. The frequency of fQRS was significantly higher in patients with hypertension than normotension (36.4% vs 17.6%, P<.05). Multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…6 - 8 Additionally, fQRS is a well described fibrotic factor in hypertension. 11 , 16 It has been demonstrated that the frequency of fQRS is significantly higher in hypertensive patients than in normotensives, 9 and non-dipper hypertensive patients have higher frequency of fQRS on ECG compared to hypertensive dippers. 10 , 11 These studies revealed that increased blood pressure levels and elevated nighttime blood pressure levels are associated with the presence of fQRS on ECG in hypertensive patients, which indicates the higher fibrotic burden within myocardium in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 - 8 Additionally, fQRS is a well described fibrotic factor in hypertension. 11 , 16 It has been demonstrated that the frequency of fQRS is significantly higher in hypertensive patients than in normotensives, 9 and non-dipper hypertensive patients have higher frequency of fQRS on ECG compared to hypertensive dippers. 10 , 11 These studies revealed that increased blood pressure levels and elevated nighttime blood pressure levels are associated with the presence of fQRS on ECG in hypertensive patients, which indicates the higher fibrotic burden within myocardium in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…8 Importantly, increased blood pressure is associated with presence of fQRS on ECG. 9 Furthermore, non-dipper hypertensive patients have higher frequency of fQRS on ECG compared to dippers, thus indicating myocardial fibrosis and higher fibrotic burden in non-dippers. 10 , 11 However, the importance and usefulness of fQRS in prehypertensive patients is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…ECG is a crucial diagnostic modality, which examines changes in cardiac electrical activity, e.g. rhythm disturbances [33,34]. ECG uses skin surface electrodes, which detect the electrical current spread throughout the body, caused by the cardiac activity.…”
Section: Electrocardiogram (Ecg)mentioning
confidence: 99%
“…In addition, electrocardiography examines changes in cardiac electrical activity, e.g. rhythm disturbances, and is thus considered to be a crucial diagnostic modality [23, 24]. Finally, pulmonary veins (PV) play a major role in triggering atrial fibrillation (AF) in humans but the mechanisms underlying PV ectopy remain unclear [25].…”
Section: Introductionmentioning
confidence: 99%